Structure-simplified and highly efficient deep blue organic light-emitting diodes with reduced efficiency roll-off at extremely high luminance. Issue 100 (30th November 2016) - Li, Xiang-Long; Liu, Ming; Li, Yunchuan; Cai, Xinyi; Chen, Dongcheng; Liu, Kunkun; Cao, Yong; Su, Shi-Jian
Abstract : Deep blue non-doped multilayer OLEDs with EQEs exceeding 5.10% and single layer devices excluding any carrier transporting materials with an EQE of 4.22% were obtained at an extremely high luminance of 10 000 cd m −2 . Abstract : Based on a series of new fluorescent emitters, deep blue non-doped multilayer OLEDs with EQEs exceeding 5.10% and single layer devices excluding any charge carrier transporting materials with an EQE of 4.22% were obtained at an extremely high luminance of 10 000 cd m −2 .